PENERAPAN ALGORITMA C.45 DALAM MENGANALISA KEPUASAN PELANGGAN PADA PENJUALAN FASHION TRIFT - Viska, Indriani Yulia; Elisa, Erlin (Computer Science and Industrial Engineering, 2023)
Fashion thrift sales have become one of the fastest growing industries, especially in this digital era. This research was conducted at one of the thrift businesses in the city of Batam, while the problem with this thrift fashion shop is the lack of stock of goods that attracts customers, because the store buys sack items, likewise this store does not serve purchase orders because items in sacks are available in various types. This study aims to analyze customer satisfaction in data mining techniques to generate new knowledge using the C4.5 classification algorithm, this algorithm uses a data mining method that carries out the process of extracting information about previous decisions. This information is used as information to form a decision tree pattern. Based on all the results of the research stages that have been carried out on the Application of the Decision Tree Classification with the C4.5 Algorithm, it can be concluded that the decision tree analysis produced by the calculation of the C4.5 algorithm shows that the variables that have the highest gain or which are the main factors in determining customer satisfaction are discount variables, product quality and price